Teletandem vs. Face-to-Face in the L2 Classroom: The Effect of Type of Media on Complexity and Accuracy - DEROBLES, Gabriela; BISTLINE-BONILLA, Chrissy (The ESPecialist, 2022)
In the past decades, foreign language classrooms at the university level have witnessed an ever-growing presence of technology. Teletandem, a collaborative and virtual medium for foreign language learning (TELLES, 2009; BENEDETTI; CONSOLO; VIEIRA-ABRAHÃO, 2010), offers language learners opportunities to receive modified input, negotiate for meaning, receive corrective, and produce modified output, all essential to second language (L2) development (LONG, 1996; GASS, 1997; GASS; MACKEY, 2007). However, an assessment of Teletandem empirical studies has revealed not only a dearth of empirical evidence in regards to the effects of this medium on L2 development, but, furthermore, a lack of research comparing Teletandem and face to face (FTF) contexts as effective media for L2 development. The present study investigates whether type of medium (Teletandem vs. FTF) has an effect on L2 learners’ oral development of lexical accuracy and global complexity. Participants were 40 advanced learners of Spanish who were randomly assigned to either a Teletandem group or a FTF group over the course of two months. The results revealed that both Synchronous Computer-Mediated Communication (SCMC) and FTF interaction had positive impacts on oral complexity, with no significant difference between the two groups. However, the results indicate that there was an advantage for Teletandem in terms of the L2 development of lexical accuracy.